Construction of a Collaborative Organizational Scheme: Regional Entrepreneurship Network of the Huila - Perdomo Charry, Geovanny (Cuadernos de Administración, 2009)
This paper about the entrepreneur culture promotion will be developed in three phases and constitutes a sequential product of three years of public and private work at Huila State in Colombia. Therefore, includes the initiatives of the previous Departmental Government with the slogan Huila Unido 2004-2007, and the current administration from Huila Naturaleza Productiva 2008-2011, the Huila’s Innovative and Technological Base Companies Incubator - Incubarhuila and Universidad Surcolombiana. The first part of the article approaches the research process of the regional social actors who develop entrepreneur and entrepreneurship activities with the aim of a state of art of entrepreneurship at a regional level; the second phase was oriented to the structure and configuration of the regional network of management of knowledge in entrepreneurs and entrepreneurship. Finally, the third section makes allusion to the implementation of the network structure and the production and initiation of a strategic plan of the same. That is to say, that the essential intent of this inter-institutional cooperation network is promoting the reticulated work in a socially responsible way with south Colombian youth, attaining improvement of their income and employment levels in a departmental plane